2014
DOI: 10.1093/ndt/gfu237
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of anti-neutrophil cytoplasm antibody-associated glomerulonephritis: evaluation of the international histological classification and other prognostic factors

Abstract: We conclude that, in our cohort of patients, the international histological classification is predictive of renal outcome in AAGN, but did not appear to be additionally informative over other established prognostic factors in multivariate analysis. However, it may be of value to combine the current histological classification with other established parameters, such as TA and percentage normal glomeruli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 27 publications
6
82
3
3
Order By: Relevance
“…The most frequent renal histological class in our analysis was sclerotic, opposite to other single-center studies and multicentric clinical trials that have validated the histological classification, where sclerotic class was absent or very infrequent [7,22,24,25]. A study that analyzed the histopathological classification in 156 Australian patients reported 20 cases (17%) with sclerotic class, and concluded that the sclerotic patterns are the lesions more reliably identified by pathologists [26].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The most frequent renal histological class in our analysis was sclerotic, opposite to other single-center studies and multicentric clinical trials that have validated the histological classification, where sclerotic class was absent or very infrequent [7,22,24,25]. A study that analyzed the histopathological classification in 156 Australian patients reported 20 cases (17%) with sclerotic class, and concluded that the sclerotic patterns are the lesions more reliably identified by pathologists [26].…”
Section: Discussioncontrasting
confidence: 83%
“…The presence of impaired renal function, and the low percentage of normal glomeruli (<25%) in our population are factors known to be associated with poor renal outcome [25,34,35].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nierenbiopsien liefern dagegen eine hohe diagnostische Ausbeute mit spezifischen Veränderun-gen (nekrotisierende Glomerulonephritis 85 %, Halbmondbildung 92 %) [2]. Die Ergebnisse der Nierenbiopsie haben zudem einen prognostischen Wert, da aktuell entzündliche (und therapeutische beeinflussbare) Veränderungen von bereits eingetretenen irreversiblen Schäden differenziert werden können, was Einfluss aufdie Wahl derTherapie habenkann [13,75,89,134,136,233,245]. Ebensokönnen Nierenfunktionseinschränkungen durch andere Begleiterkrankungen wie Diabetes mellitus oder arterielle Hypertonie abgegrenzt werden.…”
Section: Diagnostikunclassified
“…These studies have varied in size and, to our knowledge, 7 studies have included over 100 biopsies 9,10,11,12,13,14,15,16 . The first 6 of these studies have been summarized in publications by Rahmattulla, et al 17 and van Daalen, et al 18 .…”
mentioning
confidence: 99%